Caffeine Extraction from Sarawak Liberica Coffee - Li Qi, Bryan Voon; Nillian, Elexson (Journal of Coffee and Sustainability, 2024)
Liberica coffee is a minor coffee species that is cultivated all around the world. There are only a few studies conducted on this coffee species as it only occupies one percent of coffee plantations all around the world. There has yet to be a research study in Malaysia focusing on the caffeine content, the total phenolic content (TPC), and the flavonoid content (TFC) of the liberica sp. coffee mainly cultivated in Sarawak, Malaysia. Thus, in this research, Sarawak liberica sp. coffee was extracted using Soxhlet extractor using ethanol as solvent. The extracted sample was analyzed using high-performance liquid chromatography (HPLC) to identify the caffeine concentration in the sample. Colorimetric assays for phenolic compounds and flavonoids were also performed to determine the total phenolic content (TPC) and the flavonoid content (TFC). As a result, the dry basis of caffeine (w/w) in the extracted sample is 5.404%. In contrast, the total phenolic content of extracted products is 89.472 mg GAE/g of coffee beans, and the total flavonoid content of the extracted products is 308.19 mg quercetin/g of coffee beans. This research will further contribute knowledge for future Sarawak liberica sp. coffee studies.